Sounds and sweet airs : the forgotten women of classical music - Beer, Anna R., 1964- (London, England : Oneworld Publications, 2016)
Since the birth of classical music, women who dared compose have faced a bitter struggle to be heard. In spite of this, female composers continued to create, inspire and challenge. Yet even today so much of their work languishes unheard. Anna Beer reveals the highs and lows experienced by eight composers across the centuries, from Renaissance Florence to twentieth-century London, restoring to their rightful place exceptional women whom history has forgotten [Publisher description]
Notes from the silence -- [Francesca] Caccini -- [Barbara] Strozzi -- [Élisabeth] Jacquet de la Guerre -- [Marianna] Martines -- [Fanny Mendelssohn] Hensel -- [Clara] Schumann -- [Lili] Boulanger -- [Elizabeth] Maconchy -- Endnote.
Includes bibliographical references and index.
700-799
Keywords: Caccini, Francesca, -- 1587-approximately 1640.; Strozzi, Barbara, -- 1619-1677.; Jacquet de La Guerre, Elisabeth-Claude, -- 1665-1729.; Martinez, Marianne, -- 1744-1812.; Hensel, Fanny Mendelssohn, -- 1805-1847.; Schumann, Clara, -- 1819-1896.; Boulanger, Lili, -- 1893-1918.; Maconchy, Elizabeth, -- 1907-1994.; Boulanger, Lili, -- 1893-1918.; Caccini, Francesca, -- 1587-approximately 1640.; Hensel, Fanny Mendelssohn, -- 1805-1847.; Jacquet de La Guerre, Elisabeth-Claude, -- 1665-1729.; Maconchy, Elizabeth, -- 1907-1994.; Martinez, Marianne, -- 1744-1812.; Schumann, Clara, -- 1819-1896.; Strozzi, Barbara, -- 1619-1677.; 1587-approximately 1640 -- Studies; Strozzi, Barbara, -- 1619-1677 -- Studies; Jacquet de La Guerre, Elisabeth-Claude, -- 1665-1729 -- Studies; Martinez, Marianne, -- 1744-1812, -- Studies; Hensel, Fanny Mendelssohn, -- 1805-1847, -- Studies; Schumann, Clara, -- 1819-1896, -- Studies; Boulanger, Lili, -- 1893-1918, -- Studies; Maconchy, Elizabeth, -- 1907-1994, -- Studies; Women composers -- Europe -- Biography; Komponistin; Musikerin; Women composers; Europe; Biography. -- Nonfiction; Biographies